Familiar cuidador da mulher com câncer - Brandão, Patrícia Danielly de Aguiar (2016)
The aim of this study was to describe the family caregivers of women with cancer, identifying tasks and difficulties of family caregivers and identify overload and coping strategies. This study is descriptive, exploratory and convenience sample, quantitative and qualitative methods in the analysis of the results were used. Attended by 50 family caregivers of women with cancer admitted on Women's Health Reference Center in São Paulo. For this purpose, the following instruments were used: 1) sociodemographic questionnaire; 2) Inventory Zarit Overload; 3) Scale problems coping strategies. The results of this research on family caregivers are consistent with findings in the literature that describe the caregiver as belonging predominantly to the female population, the majority of caregivers are dedicated full time to the family and are inexperienced when it comes take care of other sick people. The data suggest that there are overload on family caregivers, since assumed the role of caregiver and adopt with greater intensity the coping strategies focused on the problem. The results guide the importance of health professionals to consider sick person and the family caregiver as care unit, as this caregiver is a key player in sickening the way and is conducive to feelings such as fear and anxiety, as well as stress and overload due the care that directs the patient family. Has it that the family caregiver is a unique, sensitive figure, often overlooked and ignored, it needs care and attention to minimize the negative implications and help maximize their capabilities to face care